2012
DOI: 10.1111/j.1365-3040.2012.02506.x
|View full text |Cite
|
Sign up to set email alerts
|

The natural compound trans‐chalcone induces programmed cell death in Arabidopsis thaliana roots

Abstract: Chalcone (1,3-diphenyl-2-propen-1-one) is an aromatic ketone precursor of important molecules in plants such as flavonoids or anthocyanins. Its phytotoxicity has been demonstrated on different plant species, but to date little is known about the mechanisms of action of this secondary metabolite at plant cellular level. Detailed analysis by light and transmission electron microscopy (TEM) was conducted to examine the root meristems' ultrastructure of control and chalcone-treated Arabidopsis seedlings. Mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 58 publications
3
44
1
2
Order By: Relevance
“…Consistent with other assays, trans-chalcone inhibited root growth at very low concentrations (Díaz-Tielas et al, 2012), with a 50% reduction of root growth (IC 50 ) at only 35 μM and 80% reduction (IC 80 ) at 73 μM. Furthermore, chalcone induced PCD in Arabidopsis roots and loss of photosynthetic pigments at only 35 μM.…”
Section: Phytotoxicitysupporting
confidence: 86%
See 2 more Smart Citations
“…Consistent with other assays, trans-chalcone inhibited root growth at very low concentrations (Díaz-Tielas et al, 2012), with a 50% reduction of root growth (IC 50 ) at only 35 μM and 80% reduction (IC 80 ) at 73 μM. Furthermore, chalcone induced PCD in Arabidopsis roots and loss of photosynthetic pigments at only 35 μM.…”
Section: Phytotoxicitysupporting
confidence: 86%
“…As lignin synthesis is necessary for plant growth and development, these studies suggested that the inhibition of the enzyme 4CL by chalcones, and the consequent lower rate in the synthesis of lignin, may be the reason for the inhibited plant growth. Further studies demonstrated a correlation between the inhibition of root growth and the strong decline in the activity of root peroxidases (Díaz-Tielas et al, 2012), implicated in lignin biosynthesis and ROS production (Chen and Schopfer, 1999), compounds necessary for cell growth and differentiation.…”
Section: Phytotoxicitymentioning
confidence: 98%
See 1 more Smart Citation
“…Abnormal cell division of plants with aberrant formations and less root hairs were characteristic of allelochemical-treated roots. [43] Changes in auxin content in treated roots could have played a role in the absence of root hairs, [44] as root hairs formation is sensitive to hormonal and environmental factors [45] and the local presence of auxin and expansions are required for the growth and development of root hairs.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous damage of mitochondria becomes irreversible and ensures cell death (Van Loo et al [2002]). Diaz-Tielas et al ([2012]) showed that alteration of mitochondrial membranes, swollen mitochondria, and the induction of irreversible cell death were due to the phytotoxicities of chalcone on Arabidopsis thaliana (L.) Heynh. seedlings.
Figure 7 TEM micrographs of M .
…”
Section: Resultsmentioning
confidence: 99%